1992
DOI: 10.1111/j.1464-5491.1992.tb01900.x
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Gestational Diabetes in Women from Ethnic Minority Groups

Abstract: The influence of ethnic origin, body mass index, and parity on the frequency of gestational diabetes was assessed in 11,205 consecutive women attending a multiracial antenatal clinic in London, where all women were screened for gestational diabetes. Logistic regression was used to model the relationship between gestational diabetes and ethnic origin, age, body mass index (BMI), and parity. Results were presented as adjusted odds ratios, where the reference categories are White women, age < 25 years, BMI < 27, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
166
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(189 citation statements)
references
References 13 publications
21
166
1
1
Order By: Relevance
“…These findings are consistent with earlier reports, which (Dornhorst et al, 1992), and high parity (Moses, l996) are risk factors for gestational diabetes. Approximately 53% of the GDM women were of African ancestry.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are consistent with earlier reports, which (Dornhorst et al, 1992), and high parity (Moses, l996) are risk factors for gestational diabetes. Approximately 53% of the GDM women were of African ancestry.…”
Section: Discussionsupporting
confidence: 94%
“…Asian women had a significantly higher prevalence of gestational diabetes compared with Caucasians. This observation is consistent with previously published studies (45)(46)(47)(48). Although the exact reasons for higher incidence of gestational diabetes in Asians are unknown, the differences in lipid and carbohydrate metabolism between Asian and Caucasian women may provide some explanation for this finding (46).…”
Section: Discussionsupporting
confidence: 92%
“…Studies of type 2 diabetes mellitus show that the first and the second generation of Japanese born in the USA present a gradually higher prevalence when compared to Japanese born in Japan and even greater than those who are residents of Japan 50 . Dornhorst et al 51 , in London, found ethnic origin to be a stronger predictor of gestational diabetes mellitus than age, BMI or parity, and a similar result was also found by Khine et al 52 among pregnant American women, when they evaluated prevalence of gestational diabetes mellitus stratified by race and age. Clear racial differences had also been found in the study of nurses, in which women who were Afro-American, Hispanic or that had Asian ethnicity had a significantly increased risk of gestational diabetes mellitus, when compared with whites, even after adjustment for BMI, age, family history of diabetes mellitus, level of physical activity and parity.…”
Section: Race Ethnicitysupporting
confidence: 59%